2006
DOI: 10.1007/s10549-006-9450-2
|View full text |Cite
|
Sign up to set email alerts
|

A synthetic uracil derivative with antitumor activity through decreasing cyclin D1 and Cdk1, and increasing p21 and p27 in MCF-7 cells

Abstract: The anticarcinogenic potential of (RS)-1-(2,3-dihydro-5H-1,4-benzodioxepin-3-yl)uracil (DBDU), with the naturally occurring pyrimidine base uracil, is reported against the MCF-7 cancer cell line. The arrest in the G0/G1 and G2/M cell cycle phases was accounted for by decrease in the expression of the cyclin D1 and Cdk1 proteins, and increase in p21 and p27 proteins. Using a reverse transcription-polymerase chain reaction-based assay at a dose of 5 muM of DBDU cyclin D1 mRNA was decreased, suggesting that DBDU … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…The confocal microscopy study confirmed these results (Figure 3f–j). In fact, it is known to be difficult to demonstrate programmed cell death by known apoptosis-inducing agents in the MCF-7 human breast cancer cell line, and only a few cytotoxic agents have been found to act preferentially via an apoptotic mechanism in human breast cancer cells [38,39]. …”
Section: Resultsmentioning
confidence: 99%
“…The confocal microscopy study confirmed these results (Figure 3f–j). In fact, it is known to be difficult to demonstrate programmed cell death by known apoptosis-inducing agents in the MCF-7 human breast cancer cell line, and only a few cytotoxic agents have been found to act preferentially via an apoptotic mechanism in human breast cancer cells [38,39]. …”
Section: Resultsmentioning
confidence: 99%
“…23,24 5-FU plays an important role in standard chemotherapy protocols for a range of solid tumors, including breast and colorectal cancers. 20,21 Considering the carcinogenic and mutagenic effects of Cd on healthy living cells, it seems beneficial to use a cancer cellular line, such as MCF-7.…”
Section: Introductionmentioning
confidence: 99%
“…Although Cyclin D1 is shown to regulate mitochondrial function [24] and MnSOD activity [32], the exact mechanism in Cyclin D1-controlled MnSOD activity is unknown. Here, we found that a substantial amount of Cyclin D1 and CDK4 was localized in mitochondria in HK18 cells after LDIR with a peak accumulation similar to MnSOD enzymatic activation without evident increase in cytosolic fractions (Fig.…”
Section: Resultsmentioning
confidence: 99%